A COHESIVE HARMONY OF READER’S LETTERS COLUMN IN “TIME” AND “THE JAKARTA POST” - Demantik, Maman (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2018)
This research is done by using cohesive harmony analysis. It is to describe how the two letter texts written by native (TIME) and non-native (The Jakarta Post) senders can be rated coherent and readable by the native readers. Then to compare how the two non-native letter texts can enjoy the same degree of linguistic coherence as the two native ones. Based on the analyses, the two letter texts in English newspaper written by native and non-native are judged and determined coherent by native readers. the texts are readable and comprehendable by general readers. The evidences of the coherence are those two-letter texts have fulfilled all the measures of coherence in cohesive harmony analyses.